ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PDRB DAN DISPARITAS PENDAPATAN DI PROVINSI JAWA TIMUR - Mulyani, Cici Sri; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2022)
This study was conducted to analyze the factors that influence GRDP and income disparities in East Java Province for the 2008-2019 period. The research method used in this study is a quantitative research method using panel data analysis and multivariant analysis and the software used is Eviews. The results showed that population density, Human Development Index, Regional Original Income had a positive and significant effect on GRDP, meanwhile the Open Unemployment Rate had no significant effect in a positive direction and Capital Expenditure had a significant and negative effect on GRDP, and GRDP had a significant effect. and negative on income disparity in East Java Province.